Giant Vesicle Calculus Presenting With Azotemia and Hydroureteronephrosis: A Case Report - Anjali Joshi; Parikshit Prasai; Mandish Prasad Phuyal; Pooja Rokaya; Prajwal Paudyal (Clinical Case Reports)
ABSTRACT The term “giant vesicle calculus” refers to the urinary bladder stone which is more than 4 cm in its largest diameter. Giant vesical calculus weighing more than 100 g is a rare entity. We report a case of a 63‐year male with giant vesicle calculus (measuring 6 × 3 cm) presenting with azotemia and hydroureteronephrosis. Abdominal Ultrasonography confirmed the finding of the vesical calculus with evidence of moderate to gross bilateral hydroureteronephrosis along with diverticulum with thickened and echogenic debris in the urinary bladder lumen suggestive of cystitis. He was then advised for a computerized tomography scan of the kidneys, ureters, and bladder (CT KUB) which revealed a lamellated hyperdense calculus measuring 5.92 × 5.5 × 4.37 cm3 of +1542 Hounsfield Units in bladder lumen. He was planned for cystolithotomy which revealed a 6 × 3 cm2 solitary calculus. After discharge from the hospital, the patient came for a follow up consultation during which no new problems were identified.